Optimization and Validation of Indirect ELISA Using Truncated TssB Protein for the Serodiagnosis of Glanders amongst Equines - Harisankar Singha; Praveen Malik; Sachin K. Goyal; Sandip K. Khurana; Chiranjay Mukhopadhyay; Vandana K. Eshwara; Raj K. Singh (The Scientific World Journal)
Objective. To express truncated TssB protein of Burkholderia mallei and to evaluate its diagnostic efficacy for serological detection of glanders among equines. Materials and Methods. In an attempt to develop recombinant protein based enzyme-linked immunosorbent assay (ELISA), N-terminal 200 amino acid sequences of B. mallei TssB protein—a type 6 secretory effector protein—were expressed in prokaryotic expression system. Diagnostic potential of recombinant TssB protein was evaluated in indirect ELISA using a panel of glanders positive (n=49), negative (n=30), and field serum samples (n=1811). Cross-reactivity of the assay was assessed with equine disease control serum and human melioidosis positive serum. Results. In comparison to CFT, diagnostic sensitivity and specificity of ELISA were 99.7% and 100%, respectively. Conclusions. The indirect ELISA method using the truncated TssB offered safer and more rapid and efficient means of serodiagnosis of glanders in equines. These data highlight the use of TssB as potential diagnostic antigen for serological diagnosis of glanders.